PELAKSANAAN PROMOSI GUNA MENINGKATKAN VOLUME PENJUALAN - Wahyuni Sri Astutik (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
In the implementation of promotions in order to increase sales volume at the Pangkat - Kediri tile company, an analysis result of 6.00 was obtained which states that the relationship between promotion and sales volume is strong. Because promotion is one of the determining factors for the success of every company in producing to selling their products to consumers.Because the promotion includes many things starting from product strategy to product marketing / sales. However, companies certainly cannot only focus on promotional activities, because the four elements of marketing strategy (price, promotion, distribution and production) cannot be separated. So companies should be able to combine marketing strategies appropriately, so that the company is able to achieve the desired targets, namely achieving maximum profit. In order to introduce its company products to the public with advertising media is very important. Because with this advertising effort, society knows advantages that accompanied these products, so that the company's expectations for sales to increase will be even greater and its profits will also increase.